SOCIO-ECONOMIC DEVELOPMENT OF TOLONDADU II VILLAGE COMMUNITY 2012-2022 - Alya Paputungan; Tonny Iskandar Mondong; Helman Manay (Satmata: Journal of Historical Education Studies, 2025)
This study aims to describe the socio-economic development of the Tolondadu II Village community, Bolaang Uki District, South Bolaang Mongondow Regency, for the period 2012–2022. The method used is historical research with interview, observation, and documentation study techniques. The research respondents consisted of community leaders, farmers, fishermen, and village officials who were selected purposively. Data were described through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate an increase in the community's economy as reflected in increased income and business activities, although agricultural and fishery production facilities are still simple and government support is limited. Modernization through technology, education, and infrastructure has had a positive impact on community welfare. Social change is also evident in the increased community participation in productive economic activities. In general, the development of Tolondadu II Village shows a gradual pattern towards economic independence, although still facing resource limitations.